2011
DOI: 10.1098/rsbl.2011.0320
|View full text |Cite
|
Sign up to set email alerts
|

Leeches run cold, then hot

Abstract: Food processing is costly, potentially limiting the energy and time devoted to other essential functions such as locomotion or reproduction. In ectotherms, post-prandial thermophily, the selection of a warm environmental temperature after feeding, may be advantageous in minimizing the duration of this elevated cost. Although present in many vertebrate taxa, this behaviour had not previously been observed in invertebrates. Sanguivorous leeches ingest large blood meals that are costly to process and limit mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The higher amount of saliva secretion recorded at 37ºC may be due to the simulation of the temperature of the phagostimulatory solution to that of body temperature of the host. This result corroborated with one study that shows leeches prefer feeding at warmer temperatures (Peterson et al 2011) [12] . Hence, our trial also revealed that the Indian cattle leeches usually bite repeatedly upon warm parafilm surfaces.…”
Section: Discussionsupporting
confidence: 90%
“…The higher amount of saliva secretion recorded at 37ºC may be due to the simulation of the temperature of the phagostimulatory solution to that of body temperature of the host. This result corroborated with one study that shows leeches prefer feeding at warmer temperatures (Peterson et al 2011) [12] . Hence, our trial also revealed that the Indian cattle leeches usually bite repeatedly upon warm parafilm surfaces.…”
Section: Discussionsupporting
confidence: 90%
“…Whilst the association between some herbivorous diets and a warmer body is clear, the precise physiological mechanism is not. It has long been argued that herbivores require a warmer body to support fermentation by gut microbes, but all digestive processes will proceed faster in a warmer body (Wang et al ., ) and many ectotherms select a warmer microenvironment when digesting food (Lang, ; Petersen et al ., ). The intriguing question is why the trade‐off between enhanced rates of energy acquisition and the associated increased metabolic costs should be at different temperatures for different diets.…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between host size and leech recruitment is consistent with previous findings, in that in some instances behavioural heterogeneity can be attributed to social and territorial conflicts between individual crabs of the same gender ( Wada, 1993; Milner et al, 2010; Smith et al, 2010 ). Finally, since leeches are known to have well-developed sensory systems that allow them to respond to specific situations ( Gaudry et al, 2010; Petersen et al, 2011 ), the differences observed between male and female hosts might also arise from an ability of the leech to recognize the gender of the host crab.This ability has not been demonstrated, however, and appears unlikely.…”
Section: Discussionmentioning
confidence: 99%